The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1080/02786828408959014
|View full text |Cite
|
Sign up to set email alerts
|

Lidar and Balloon-Borne Cascade Impactor Measurements of Aerosols: A Case Study

Abstract: Aerosol size distributions, elemental components, complex refractive indices, extinction profiles and extinctionto-backscatter ratios have been measured and inferred from balloon-borne cascade impactor and lidar observations made during a cooperative joint experiment conducted during the period 4-10 April, 1980 in Tucson, AZ. Size distributions obtained from quartz crystal microbalance (QCM) cascade impactor measurements at different heights (1 to 1000 m) and times over a period of several days were fairly sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…A Junge distribution of slope v = 3 is also included because Junge-type distributions with slopes bounded between -2 < v < 3 are also frequently obtained from inversions of Tucson spectral optical depth data . The final distribution included in Figure 3, referred to as the mean balloon impactor distribution, is the average of several balloon-borne cascade impactor measurements made in Tucson during April 1980, as previously reported by Reagan et al (1984). With the exception of the v = 3 Junge distribution, they all display a noticeable peaking in the large or coarse particle mode.…”
Section: Assessment Of S Measurementsmentioning
confidence: 70%
See 4 more Smart Citations
“…A Junge distribution of slope v = 3 is also included because Junge-type distributions with slopes bounded between -2 < v < 3 are also frequently obtained from inversions of Tucson spectral optical depth data . The final distribution included in Figure 3, referred to as the mean balloon impactor distribution, is the average of several balloon-borne cascade impactor measurements made in Tucson during April 1980, as previously reported by Reagan et al (1984). With the exception of the v = 3 Junge distribution, they all display a noticeable peaking in the large or coarse particle mode.…”
Section: Assessment Of S Measurementsmentioning
confidence: 70%
“…Intercomparative experiments involving airborne direct aerosol measurements as well as crosschecks with other remote sensing measurements (Reagan et al, 1977(Reagan et al, ,1984Spinhrne et al, 1980) have demonstrated that the slant-path lidar technique can be employed with good success. In addition, the solution procedure produces standard deviation estimates for the retrieved values of Sa, P,(r), and a,(r).…”
Section: Measurement Progedure and Analysis Techniquesmentioning
confidence: 99%
See 3 more Smart Citations